INSTRUCTION IN ACCOUNTING FOR LIBERAL EDUCATION. - Shaulis, L. L. (The Accounting Review, 1930)
This article makes an attempt to rationalize the relationship of accounting instruction to a liberal course of study. The lack of uniformity as to the extent and as to the type of accounting instruction offered by liberal arts colleges leads one to believe that rationalization upon this subject has not been conclusive. For the last thirty years, the addition of courses in Economics, Commerce, and Business Administration is one of the outstanding developments in the content of the curricula of colleges and universities in the U.S. The principle which differentiates schools or courses of instruction is to be found in the fundamental purpose which they are designed to serve. In a professional school courses are designed and taught with the idea of preparing men for some special function or profession in life. Accounting maybe described as intelligent counting. It is as essential in the determination of the facts of economic and business experience as are sound and adequate laboratory and field methods in the field of natural science.